Shortage of antidiabetic and antihypertensive in the context of the initial stage of the COVID-19 pandemic in Peru - Herrera-Añazco, Percy (2021)
Background: An adequate supply of medicines in health establishments will increase the possibility of adequate control of hypertension and diabetes. Objective: To determine the shortage of antidiabetic and antihypertensive drugs at the national level in the context of the initial stage of the COVID-19 pandemic in Peru. Material y methods: Analysis of the "Sistema Integrado de Suministro de Medicamentos e Insumos Médicos Quirúrgicos" (SISMED) Database, between June 13th and July 15th, 2020, according to the "National list for medicines of essential medicines" (PNUME) of Ministry of health. Results: And between 4 and 96% of the departments have a total shortage of at least one antidiabetic, and 4% and 96% of at least one antihypertensive. The most depleted antidiabetic was Metformin 500 mg, and the most depleted antihypertensive drugs were Labetalol 5 mg / ml iny, Atenolol 50 mg tab and Carvedilol 6.25 mg tab. The percentage of distribution was higher in hospitals and specialized institutes in comparison with primary health facilities. Conclusions: There is a shortage of antihypertensive and antidiabetic drugs in health centers in Peru. © 2021 Medical Body of the Almanzor Aguinaga Asenjo National Hospital.